Antioxidant Properties Mediate Nephroprotective and Hepatoprotective Activity of Essential Oil and Hydro-Alcoholic Extract of the High-Altitude Plant Skimmia anquetilia - Neha Kukreti; Havagiray R. Chitme; Vinay K. Varshney; Basel A. Abdel-Wahab; Masood Medleri Khateeb; Mohammed Shafiuddin Habeeb (MDPI AG, 2023)
There are many high-altitude plants such as Skimmia anquetilia that are unexplored for their possible medicinal values. The present study was conducted to examine the antioxidant activities of Skimmia anquetilia (SA) using in vitro and in vivo models. The SA hydro-alcoholic extracts were investigated using LC-MS for their chemical constituents. The essential oil and hydro-alcoholic extracts of SA were evaluated for pharmacological properties. The antioxidant properties were evaluated using in vitro DPPH, reducing power, cupric reducing antioxidant power, and metal chelating assays. The anti-hemolytic activity was carried out using a human blood sample. The in vivo antioxidant activities were evaluated using CCL4-induced hepatotoxicity and nephrotoxicity assay. The in vivo evaluation included histopathological examination, tissue biochemical evaluation such as the kidney function test, catalase activity, reduced glutathione activity, and lipid peroxidation estimation. The phytochemical investigation showed that the hydro-alcoholic extract contains multiple important active constituents such as L-carnosine, acacetin, linoleic acid, leucylleucyl tyrosine, esculin sesquihydrate, etc., similar to the components of SA essential oil reported in a previous study. The high amount of total phenolic content (TPC) and total flavonoid content (TFC) reflect (p < 0.001) a high level of reducing power, cupric reducing, and metal chelating properties. This significantly (p < 0.001) inhibited enlargement of the liver, with a significant reduction in ALT (p < 0.01) and AST (p < 0.001). Highly significant improvement in the functioning of the kidney was noted using the blood urea and creatinine (p < 0.001) levels. Tissue-based activities showed a major rise in catalase, reduced glutathione, and reduced lipid peroxidation activities. We conclude from this study that the occurrence of a high quantity of flavonoid and phenolic contents had strong antioxidant properties, leading to hepatoprotective and nephroprotective activity. Further active constituent-specific activities should be evaluated.